Pendekatan Sistem Dalam Menganalisis Misi Lembaga Pendidikan - Abdul Fattah Nasution; Khoiriyah Syaharani Ritonga; Nazwa Alisya Harahap; Saddam Maulana (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The systems approach is an effective method in analyzing the mission of educational institutions, where the complexity and interdependence between components in the education system can be understood holistically. This article aims to explore how the systems approach can be used to identify, formulate, and disseminate the mission of educational institutions, and its impact on the development of better education policies. By using a systems framework, researchers can explore the relationship between the vision, values, and goals of educational institutions and how these elements contribute to the achievement of expected educational outcomes. The results show that the systems approach not only helps in formulating a clearer and more measurable mission, but also increases the involvement of all parties in the process of formulating the mission. This creates a sense of ownership and shared responsibility for achieving the goals of the institution, this article also discusses the challenges faced in implementing the systems approach, such as resistance to change and a lack of understanding of the importance of collaboration between elements in the education system.